Template requirements for the initiation of adenovirus DNA replication. - Challberg, M D (1984)
The first step in the replication of the adenovirus genome is the covalent attachment of the 5'-terminal nucleotide, dCMP, to the virus-encoded terminal protein precursor (pTP). This reaction can be observed in vitro and has been previously shown to be dependent upon either viral DNA or linearized plasmid DNA containing viral terminal sequences. Plasmids containing deletions or point mutations within the viral terminal sequence were constructed by site-directed mutagenesis. In the case of linear double-stranded templates, pTP-dCMP formation required sequences located within the first 18 base pairs of the viral genome. This sequence contains a segment of 10 base pairs that is conserved in all human adenovirus serotypes. Point mutations within the conserved segment greatly reduced the efficiency of initiation, while a point mutation at a nonconserved position within the first 18 base pairs had little effect. Single-stranded DNAs can also support pTP-dCMP formation in vitro. In contrast to the results obtained with duplex templates, experiments with a variety of single-stranded templates, including phage M13-adenovirus recombinants, denatured plasmids, and synthetic oligodeoxynucleotides, failed to reveal any requirements for specific nucleotide sequences. With single-stranded templates containing no dG residues, the specific deoxynucleoside triphosphate requirements of the initiation reaction were altered.